Mindcage [videorecording (Blu-Ray + DVD)] - Borrelli, Mauro (Lionsgate, 2023)
In this spellbinding thriller, detectives Jack Doyle and Mary Kelly seek the help of an incarcerated serial killer name The Artist when a copycat killer strikes. While Mary searches for clues in The Artist₂s brilliant but twisted psyche, she and Jack are lured into a diabolical game of cat and mouse, racing against time to stay one step ahead of The Artist and his copycat.